The Effectiveness of Immunization Education on Parents' Knowledge in Advanced Immunization during the Covid-19 Pandemic at the Kampung Sawah Puskesmas in 2022 - Maesaroh Binti Mastiri; Omega DR Tahun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Follow-up immunization repeats basic immunization to extend the protection period or maintain the immunity level of children who have received basic immunization. Follow-up immunizations are given to children under two years of age, namely diphtheria, pertussis, tetanus, hepatitis B, pneumonia, meningitis and measles. The COVID-19 pandemic in immunization coverage is not reaching the target. The purpose of this study was to determine the effectiveness of education on parents' knowledge of implementing advanced immunization. This type of research is a quasi-experimental, the number of samples is 30, the type of statistical test is the paired sample t test, the sampling technique is purposive sampling. The results of statistical tests showed that health education was effective in increasing the knowledge of parents in implementing follow-up immunizations for infants aged 12-24 months (sig. 0.000 <0.05). Health education needs to be optimized in order to increase the knowledge of parents to carry out follow-up immunizations for babies in this pandemic era.